2020
DOI: 10.1002/prep.202000114
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Comparison of Selected Blue Flame Pyrotechnics

Abstract: In this research, 10 different pyrotechnic blue flame compositions were designed and compared. Chromaticity and luminosity parameters of the flame were measured using Ocean Optics JAZ-ULM VIS-Spectrometer equipped with a cosine corrector. Color saturation, luminous intensity, specific luminous intensity, oxygen balance, burn rate, actual and theoretical maximum density, color coordinates (X, Y) are presented and discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 8 publications
0
14
0
Order By: Relevance
“…Thermal analysis is one of the important methods for evaluating the thermal stability of energetic materials. 32,33 Therefore, we conducted DSC-TG and DTA testing to analyze the thermal behavior of ECP-1 (test conditions: heating rate: 5 1C min À1 , atmosphere: N 2 ).…”
Section: Physicochemical Stability Analysismentioning
confidence: 99%
“…Thermal analysis is one of the important methods for evaluating the thermal stability of energetic materials. 32,33 Therefore, we conducted DSC-TG and DTA testing to analyze the thermal behavior of ECP-1 (test conditions: heating rate: 5 1C min À1 , atmosphere: N 2 ).…”
Section: Physicochemical Stability Analysismentioning
confidence: 99%
“…It found that the Lsp value is comparable to the total amount of oxygen and nitrogen present in the gas generating additive [19]. Further, blue color, with the wavelength ranging from 425 -500 nm, is commonly generated from copper based-compounds such as CuCO3.Cu(OH)2 [13], Cu powder electrolytic, basic copper carbonate Cu2(CO3)(OH)2, copper benzoate, Paris green, CuOCl, CuO [20] and Cu3Cl3 [21]. Juknelevious et al [22], reported the use of the pyrotechnic composition to develop the blue strobe using a formulation called Jennings-White's blue strobe No.5, which could maintain the flame color quality [22].…”
Section: Introductionmentioning
confidence: 99%
“…Classical energetic ionic salts are formed by combining organic skeleton molecules with oxidizing acids (such as HClO 4 and HNO 3 ). Among them, most organic skeleton molecules come from heterocyclic rings, such as triazole and tetrazole, which can be modified by adding groups such as −NH 2 , −OH, and −NO 2 to change their N and O contents. , Oxidative acid ions can make great contributions to improving oxygen balance and detonation performance. , ECPs are obtained by the coordination covalent bond between ligands and metal ions. The difference is that the ligands here are diverse.…”
Section: Introductionmentioning
confidence: 99%